Vitamin contents and antioxidant capacity of hydroponic grown sweet basil inoculated with endophytic bacteria - Campos Espinosa, Gabriela Y.; Dörr de Quadros, Patricia; Fulthorpe, Roberta R.; Tsopmo, Apollinaire (Frontiers in Sustainable Food Systems, 2022)
The aim of this study was to assess the effect of inoculated endophytic bacteria on the concentrations of vitamins E (tocopherols), K (phylloquinone), B1 (thiamine), B2 (riboflavin), C (ascorbic acid) and the peroxyl radical scavenging capacity of hydroponically grown sweet basil. Endophytic strains were all isolated from hydrocarbon-stressed herbaceous plants or from basil showing superior growth. Plants inoculated with the endophytes displayed up to 40% increase (p < 0.05) in the concentration of the reduced form of vitamin C relative to control [0.56 mg/g fresh weight (FW)] which indicated less oxidative stress in the presence of endophytes. In the case of γ-tocopherol, the highest content [25.8 μg/g of fresh weight (FW)] in inoculated basils was significantly higher compared to control plants (18.5 ± 1.2 μg/g FW) (p < 0.05). Antioxidant activity (ROO∙ radicals scavenging) was as high as 94 ± 4 μM Trolox equivalents (TE)/g FW vs. 53 ± 5 μM TE/g FW for the control basil. Concentrations of vitamins C, B1, and B2 were not affected by most strains. The results showed that endophytic bacteria have the capacity to alter free radical quenching capacity and vitamin concentrations in basil plants and, that their effect is strain and nutrient dependent.